The IMPROVING THE MECHANISM OF INCREASING COMPETITIVENESS OF SMALL BUSINESS ENTITIES IN LOCAL CONSUMER MARKETS - Tajibayev, Komiljon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article examines the issues of assessing the competitiveness of small business enterprises. The competitiveness of the enterprise can be determined depending on the dynamics of the integral indicator of the enterprise's competitiveness, taking into account the change in the share of sales of each of the enterprise's goods on the market and the change in their share in the enterprise's sales volume. The issues of evaluating the competitiveness of the enterprise with its production profitability, and comparing it with the average industrial profitability have been studied. Conclusions and suggestions have been developed regarding the problems.